Snow, ponds, trees, and frogs: how environmental processes mediate climate change impacts on four subarctic terrestrial and freshwater ecosystems - M. Morison; N.J. Casson; S. Mamet; J. Davenport; T. Livingston; L.A. Fishback; H. White; A. Windsor (Canadian Science Publishing, 2023)
Amplified warming in subarctic regions is having measurable impacts on terrestrial and freshwater ecosystem processes. At the boundary of the discontinuous and continuous permafrost zones, and at the northern extent of the boreal forest, the Hudson Bay Lowlands has experienced, and is projected to continue to experience dramatic rates of climate change in the coming decades. In this review, we explore the impacts of climate change on terrestrial and freshwater ecosystems in the Hudson Bay Lowlands and other environmental processes that mediate these impacts. We surveyed published literature from the region to identify climate indicators associated with impacts on snowpacks, ponds, vegetation, and wood frogs. These climate indicators were calculated using statistically downscaled climate projections, and the potential impacts on ecosystem processes are discussed. While there is a strong trend towards longer and warmer summers, associated changes in the vegetation community mean that snowpacks are not necessarily decreasing, which is important for freshwater ponds dependent on snowmelt recharge. A clear throughline is that the impacts on these ecosystem processes are complex, interconnected, and nonlinear. This review provides a framework for understanding the ways in which climate change has and will affect subarctic regions.